Penambahan Arang Sekam, Kotoran Domba dan Cocopeat untuk Media Tanam - Asroh Asroh; Titin Patimah; Nanda Delvia Meisani; Rendi Irawan; Afton Atabany (Jurnal Pusat Inovasi Masyarakat (PIM), 2021)
The activity of making planting media for indigofera plants was carried out on July 18, 2020 in the farm area owned by one of the assistants of the Agriculture Office, namely Mr. The purpose of this activity is to make a planting medium for the seedbed of Indigofera zollingeriana from a mixture of several ingredients, namely soil, sheep dung, husk charcoal and cocopeat. The treatment was to compose organic matter with soil mixture. The results showed that the mixture of organic growing media in the form of husk charcoal, sheep dung, cocopeat and soil had a very significant effect on plant height. The best mix of organic planting media for the growth and yield of indigofera plants and for vertical gardens is organic growing media in the form of 25% soil, 25% husk charcoal, 25% sheep dung. cocopeat 25%. Keywords: indigofera, sheep dung, husk charcoal, organic